2022
DOI: 10.1007/s40820-022-00792-x
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Low-Dose Pre-Metallation Strategy Served for Commercial Metal-Ion Capacitors

Abstract: Highlights Interfacial bonding strategy has been successfully applied to address the high overpotential issue of sacrificial additives, which reduced the decompositon potential of Na2C2O4 from 4.50 to 3.95 V. Ultra-low-dose technique assisted commercial sodium ion capacitor (AC//HC) could deliver a remarkable energy density of 118.2 Wh kg−1 as well as excellent cycle stability. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 82 publications
(40 citation statements)
references
References 44 publications
0
40
0
Order By: Relevance
“…In order to tackle these key problems, multifarious ways have been proposed, such as combining with highly conductive carbonaceous materials [ 4 , 5 ], designing greatly stable structures [ 6 , 7 ], building interfacial bonds [ 8 ], and introducing doping heteroatoms [ 9 ]. Constructing Sb 2 S 3 /carbon composite is the most common and effective strategy [ 10 12 ]. For instance, Sb 2 S 3 /sulfur-doped graphene sheets composite prepared by Liu et al showed a high-capacity retention of 83% for 900 cycles at 2 A g −1 [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to tackle these key problems, multifarious ways have been proposed, such as combining with highly conductive carbonaceous materials [ 4 , 5 ], designing greatly stable structures [ 6 , 7 ], building interfacial bonds [ 8 ], and introducing doping heteroatoms [ 9 ]. Constructing Sb 2 S 3 /carbon composite is the most common and effective strategy [ 10 12 ]. For instance, Sb 2 S 3 /sulfur-doped graphene sheets composite prepared by Liu et al showed a high-capacity retention of 83% for 900 cycles at 2 A g −1 [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that ameliorated Na 2 C 2 O 4 reported in our previous work is adopted as sacrificial © 2022 Wiley-VCH GmbH cathode additive to accomplish the mission of pre-sodiation as it can be identified as optimal candidate for scale-up production. [28] Interestingly, the pouch-type capacitors can deliver a remarkable energy density of 73.6 Wh kg -1 at the current density of 0.1 A g -1 (Figure S12b, Supporting Information) after activation within the voltage window of 4.3-0 V (Figure S12c, Supporting Information), delivering great application potential.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the sluggish diffusion kinetics of K + and the degradation of the structure due to the large radius of potassium (0.138 nm) hinder the development of anode electrodes of PIBs [5][6][7][8][9]. Carbon-based materials have acted as an important role in the construction of anode electrode engineering since it was reported that K + can be de/inserted into graphite in 2015 [10][11][12][13][14]. However, the rate performance and cycle stability of graphite as an anode are unsatisfactory due to the limited layer spacing and polarization phenomenon.…”
Section: Introductionmentioning
confidence: 99%